Diverse Anatexis in the Main Central Thrust Zone, Eastern Nepal: Implications for Melt Evolution and Exhumation Process of the Himalaya. (28th January 2022) - Liu, Shuaiqi; Zhang, Guibin; Zhang, Lifei; Wang, Shuzhen; Upreti, Bishal N; Adhikari, Danda P; Wu, Chenguang; Wang, Jiaxing
Abstract: Sitting between the Greater Himalayan sequence (GHS) and Lesser Himalayan sequence (LHS), the Main Central Thrust zone (MCTZ) has experienced multiple episodes of anatexis, which presents an opportunity to explore the nature of partial melting and its response to Himalayan orogenic processes. A series of deformed rocks, including migmatites, gneisses, and leucosomes were collected across the MCT at Arun Valley, eastern Nepal. We investigated the bulk rock major and trace elements, Sr-Nd isotopes, mineral chemistry, zircon geochronology and Hf isotopes, and conducted phase equilibria modeling. The protolith boundary between the GHS and LHS is recognized on the basis of Sr–Nd isotopes with ε Nd (0) of −16.7 to −8.0 for the GHS and −31.2 to −23.9 for the LHS. Samples from both the GHS and LHS have undergone partial melting, as revealed by in situ leucosomes at outcrops and melt inclusions at thin-section scale. Leucosomes separated from their host rocks are divided into four groups: those derived from hydration melting, muscovite dehydration melting, amphibole dehydration melting, and feldspar accumulation. Phase equilibria modeling results for the GHS migmatite show isothermal decompression from peak P–T conditions of 11 kbar and 795°C, accompanied by muscovite dehydration melting evolving into biotite dehydration melting. In contrast, rocks from the LHS are modeled to have undergone hydration melting at P–T conditions of 9 kbar and 685°C. Zircon U–Pb geochronology suggests that long-lived partial melting (35–13 Ma) occurred in the MCTZ. Moreover, anatectic zircon Hf isotopes show that the protoliths for partial melting changed from the GHS to the LHS with εHf (t) of −19.4 to −5.7 during the early Miocene, and lower values of −42.5 to −16.7 during the middle to late Miocene. These zircon geochemical results indicate that hydrous metasediments from the LHS were progressively accreted to the base of the GHS, resulting in hydration melting of both the GHS and LHS assisted by MCT. The timing of activity of the MCT is constrained to 25–13 Ma, coeval with movement of the South Tibetan detachment system. Integration of petrogenetic modeling, the chronology of partial melting, and metamorphic P–T paths allows us to propose that thickened Himalayan crust was heated from the middle to late Eocene, and widespread anatexis occurred during the Oligocene to middle Miocene, forming a large-scale melt channel. The hot GHS channel flow moved upward in association with the synchronous activity of the MCT system, triggered intense dehydration of LHS metasediments, resulting in fluid-present melting in both the GHS and LHS during middle to late Miocene, and the formation of leucogranite with mixture features of GHS and LHS. Furthermore, with the cooling of the melt channel, duplexing has gradually operated since the middle to late Miocene in the shallow crust.